The Influence of Different Winemaking Techniques on the Extraction of Grape Tannins and Anthocyanins - Nel, A.P.; van Rensburg, P.; Lambrechts, M.G. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to determine the effect of different maceration techniques on the extraction of grape tannins and anthocyanins. Two cultivars (Cabernet Sauvignon and Shiraz) were harvested in two different climatic regions (Durbanville and Simondium) at two different ripeness levels for the 2008 and 2009 harvest seasons. Five basic winemaking processes were applied, namely a normal alcoholic fermentation (C), enzyme treatment (E), cold soaking (CM), post-maceration (PM), and a combination of cold and post-maceration (CM+PM). At harvest the phenolic ripeness was determined with the Glories method, while the tannin concentration was determined with the methyl cellulose (MCP) method. The grapes in the warmer area had higher tannin levels than grapes harvested in the cooler area in both years. In the 2009 harvest season, the enzyme treatment extracted the highest levels of tannin. CM+PM showed the best results of tannin extraction with early ripeness (Cabernet Sauvignon), and CM with fuller ripeness in the warm area. CM showed the best results with both early and fuller ripeness levels in the cooler area. PM showed the best results with the early ripeness levels, and the E treatment with the fuller ripeness levels, in the warm area. CM+PM showed the best results with the early ripeness level in the cooler area, and varied results with the fuller ripeness levels. In both years, grapes from the cooler area contained more anthocyanin than those from the warmer area. At a fuller ripeness level (2009) the treatments had no effect.